Traumatic brain injury triggers APP and Tau cleavage by delta-secretase, mediating Alzheimer's disease pathology. (February 2020) - Wu, Zhourui; Wang, Zhi-Hao; Liu, Xia; Zhang, Zhentao; Gu, Xiaohuan; Yu, Shan Ping; Keene, C. Dirk; Cheng, Liming; Ye, Keqiang
Abstract: Traumatic brain injury (TBI) is associated in some studies with clinical dementia, and neuropathological features, including amyloid plaque deposition and Tau neurofibrillary degeneration commonly identified in Alzheimer's disease (AD). However, the molecular mechanisms linking TBI to AD remain unclear. Here we show that TBI activates transcription factor CCAAT/Enhancer Binding Protein Beta (C/EBPβ), increasing delta-secretase (AEP) expression. Activated AEP cleaves both APP and Tau at APP N585 and Tau N368 sites, respectively, which mediate AD pathogenesis by promoting Aβ production and Tau hyperphosphorylation and inducing neuroinflammation and neurotoxicity. Knockout of AEP or C/EBPβ diminishes TBI-induced AD-like pathology and cognitive impairment in the 3xTg AD mouse model. Remarkably, viral expression of AEP-resistant Tau N368A in the hippocampus of 3xTg mice also ameliorates the pathological and cognitive consequences of TBI. Finally, clinical TBI activates C/EBPβ and escalates AEP expression, leading to APP N585 and Tau N368 proteolytic cleavage in TBI patient brains. Hence, our findings support a potential role for AEP in linking TBI exposure with AD pathogenesis.